Volume 6: Turbo Expo 2003, Parts a and B 2003
DOI: 10.1115/gt2003-38270
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Labyrinth Seal Variation on Multistage Axial Turbine Flow

Abstract: The need to increase overall turbine efficiency is always a driving force for redesigning a turbine stage. In particular, the labyrinth leakage flows in the endwall regions contribute to an increase of the overall loss generation. In order to asses this mechanism, a detailed study of the effects of labyrinth seal geometry variation on the blade performance is presented. Two different shroud seal geometries have been experimentally investigated in a two stage low speed turbine facility. The seal geometries diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The measurement uncertainty of the test facility concerning total-to-static efficiency of the second stage is ±0.21%. A more detailed description of the test facility is available in Schlienger et al [20]. The stator blade row configurations differ as shown in Table 1.…”
Section: Inlet Cavity Configurationsmentioning
confidence: 99%
“…The measurement uncertainty of the test facility concerning total-to-static efficiency of the second stage is ±0.21%. A more detailed description of the test facility is available in Schlienger et al [20]. The stator blade row configurations differ as shown in Table 1.…”
Section: Inlet Cavity Configurationsmentioning
confidence: 99%
“…Schlienger et al [10] compared a rectangular cavity configuration with sharp edge corners and the one modified by placing inserts to allow a shallower injection angle. They found that the inserts reduced the strength of the passage vortex and consequently the amount of under-and overturning in the outflow near the hub.…”
Section: Introductionmentioning
confidence: 99%
“…27 Burcham et al 28 have summarized the typical labyrinth seal configurations. Schlienger et al 29 experimentally tested the aerodynamic performance of a two-stage turbine with different shroud seal geometries. It is shown that the inserts in the re-entry cavities have a positive impact on the efficiency at larger tip clearances.…”
Section: Introductionmentioning
confidence: 99%